Antiviral effects and mechanism of Ma-Xing-Shi-Gan-San on porcine reproductive and respiratory syndrome virus - Zhang, Miao; Huang, Jiankun; Chi, Qingan; Ran, Xuhua; Wen, Xiaobo (Frontiers in Microbiology, 2025)
BackgroundCurrently, vaccination has consistently posed challenges in preventing the Porcine reproductive and respiratory syndrome virus (PRRSV), so there is an urgent need for effective controlling strategies. Ma-Xing-Shi-Gan-San (MXSGS), a traditional Chinese medicine (TCM) formula used for pulmonary diseases and respiratory disorders, has proven effective in treating H1N1 and COVID-19. Herein, we evaluated whether MXSGS exhibits potent antiviral activity against PRRSV.MethodsFirst, a PRRSV-infected Marc-145 cell model was established. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and the tissue culture infective dose (TCID₅₀) assay were performed to assess the inhibitory effects of MXSGS on PRRSV during different administration stages. Network pharmacology was then employed to identify key active ingredients and core potential targets of MXSGS against PRRSV. In addition, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were conducted to elucidate the antiviral signaling pathways modulated by MXSGS. Lastly, candidate ingredients and targets were validated by molecular docking analysis.ResultsMXSGS significantly inhibited PRRSV through prophylactic and therapeutic administration and suppressed multiple phases of the viral life cycle, including attachment, internalization, replication, and release. In network pharmacology results, 82 active ingredients and 118 therapeutic targets related to MXSGS and PRRSV were identified. Among them, Calycosin, Odoratin, Glyzaglabrin, 7,2′,4′-trihydroxy-5-methoxy-3-arylcoumarin, and Eriodictyol were selected as key active ingredients. ALB, PPARG, CASP3, STAT3, TGFB1, JAK2, TLR4, PRKACA, and PRKACB were screened as potential core targets. Furthermore, pathway and functional enrichment analysis revealed that the impact of MXSGS on PRRSV mainly involved Toll-like receptor signaling pathway, typical NF-κB signaling, positive regulation of interleukin-6 production, Th17 cell differentiation, inflammatory response, and viral defense response. Lastly, molecular docking analysis indicated an excellent binding affinity between the core potential targets and key active ingredients, with all binding energies < −6.0 kcal/mol.ConclusionIn vitro experiments indicated that MXSGS exhibited considerable anti-PRRSV activity. Using network pharmacology and molecular docking approaches, five key active ingredients and six core potential targets were identified, underscoring MXSGS as a promising pharmaceutical agent for controlling PRRSV.